1988
DOI: 10.1002/jlb.43.5.445
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Respiratory Burst and Bactericidal Activity of Alveolar Macrophages From Adult and Senescent Mice

Abstract: To assess the effects of advanced age on the nonspecific antimicrobial activity of resident alveolar macrophages (AM), superoxide anion (O2-) release and the phagocytic and bactericidal capacity of cells from three genetically distinct murine strains were evaluated. In initial experiments, resident AM, obtained by bronchoalveolar lavage of pathogen-free adult female CD-1 mice and studied in suspension, were found to produce O2- spontaneously and in response to phorbol myristate acetate (PMA) snd unopsonized zy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 34 publications
3
13
0
Order By: Relevance
“…These values are similar to the normal cell profile of BALF in mice [8]. In addition, there was no significant change in the recovery rates of instilled fluid from mice of different ages.…”
Section: Resultssupporting
confidence: 71%
“…These values are similar to the normal cell profile of BALF in mice [8]. In addition, there was no significant change in the recovery rates of instilled fluid from mice of different ages.…”
Section: Resultssupporting
confidence: 71%
“…The number of resident bronchoalveolar macrophages isolated from unin fected, aged C57BL/6 mice was significantly greater than that secured from the younger animals (fig. 2); this finding confirms a simi lar observation made by this laboratory in prior studies [Esposito et al, 1988b]. More importantly, at 24 h after pneumococcal challenge, the number of neutrophils present within the bronchoalveolar spaces was sig nificantly greater in the older animals (fig.…”
Section: Pulmonary Inflammatory Responsesupporting
confidence: 80%
“…Further, our survival studies indicate that in the nonimmune, nor mal C57BL/6 mouse, advanced age does not enhance susceptibility to lethal infection with type 3 S. pneumoniae. Thus, these find ings and the results of our complementary studies of murine bronchoalveolar macro phage function [Esposito et al, 1988b;Espo sito et al, 1989] indicate that factors beyond advanced age must play prominent roles in predisposing the aged host to pneumococcal infection of the lower respiratory tract and to increasing the likelihood of a fatal out come.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…It was estimated that, because of this, no more than 1 × 10 8 P. gingivalis remained at 48 h in the Old age group, and that this is likely to be due to innate immunity. Esposit et al (10) reported that alveolar macrophages of the lungs, even in aged mice, showed some ability to kill bacteria, and there was no significance compared with young mice. IFN-γ is known to activate macrophages and to increase the production of NO.…”
Section: Figmentioning
confidence: 99%